1999
DOI: 10.1034/j.1600-051x.1999.260603.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility of putative periodontal pathogens in advanced periodontitis patients

Abstract: In the present study, the antibiotic susceptibility of most prevalent micro-organisms in advanced periodontitis patients was evaluated. In 56 patients, pooled subgingival plaque samples were taken from the deepest site of each quadrant and were cultivated anaerobically. From each patient, the 4 most frequently encountered types of bacterial colonies were subcultured and identified (Rapid ID 32 A). From all bacterial species identified in the 224 subcultures, the 4 most prevalent were used for susceptibility te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 18 publications
3
34
0
2
Order By: Relevance
“…Other investigations have also shown that anaerobic species such as P. intermedia, P. gingivalis and Fusobacterium species are highly sensitive to metronidazole (Eick et al 1999, Kleinfelder et al 1999, Poulet et al 1999). On the other hand, metronidazole-resistant strains of B. forsythus and P. gingivalis were not detected in any plaque or saliva sample before, during or after therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Other investigations have also shown that anaerobic species such as P. intermedia, P. gingivalis and Fusobacterium species are highly sensitive to metronidazole (Eick et al 1999, Kleinfelder et al 1999, Poulet et al 1999). On the other hand, metronidazole-resistant strains of B. forsythus and P. gingivalis were not detected in any plaque or saliva sample before, during or after therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier studies have used either bacteria in planktonic culture or single‐species biofilms to test the in vitro efficacy of various antibiotics. MICs for several single species isolated from subgingival plaque, including P. gingivalis and F. nucleatum , are shown to be below antibiotic concentrations achievable in GCF 13 . In terms of single‐species biofilms, one of the most studied has been P. gingivalis , which is shown to be susceptible to amoxicillin, doxycycline, and metronidazole over a period of 48 hours, albeit at higher MICs than in conventional planktonic cultures 19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…The minimum inhibitory concentration (MIC) for a number of putative periodontal pathogens is shown to be below the antibiotic concentrations achievable in GCF 13 . Nevertheless, studies on the efficacy of antibiotics have traditionally used planktonic bacterial cultures of periodontal pathogens, and in many cases, at concentrations that are not of physiologic relevance.…”
mentioning
confidence: 99%
“…The MIC 90 for Actinobacillus actinomycetemcomitans is of 3.1 g/mL. 31 To limit the development of bacterial resistance, Kleinfelder et al 32 proposed that the quantity of released antibiotic should be 100 times that of the MIC to induce a relevant clinical effect. The quantity delivered in the present experimental conditions seems to be compatible with these prescriptions as the volume in which the membrane has to release the antibiotic does not exceed 1 mL.…”
Section: Discussionmentioning
confidence: 99%